2021
DOI: 10.1145/3452379
|View full text |Cite
|
Sign up to set email alerts
|

Pliers

Abstract: Programming language design requires making many usability-related design decisions. However, existing HCI methods can be impractical to apply to programming languages: languages have high iteration costs, programmers require significant learning time, and user performance has high variance. To address these problems, we adapted both formative and summative HCI methods to make them more suitable for programming language design. We integrated these methods into a new process, PLIERS, for designing programming l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Notable works within this area include the Whyline [30], a debugger with explanations, and the study of natural programming [43], i.e., based on programming user studies where the subjects have no prior conceptions of programming to bias their experiences. In recent years, this line of work has been operationalized in the PLIERS design framework [12].…”
Section: User-centered Pls and Programmer Experiencementioning
confidence: 99%
“…Notable works within this area include the Whyline [30], a debugger with explanations, and the study of natural programming [43], i.e., based on programming user studies where the subjects have no prior conceptions of programming to bias their experiences. In recent years, this line of work has been operationalized in the PLIERS design framework [12].…”
Section: User-centered Pls and Programmer Experiencementioning
confidence: 99%
“…A potentially significant outcome of research efforts on the comprehension of specifications can be translated to a better design of specification languages, perhaps inspired by the work on natural programming [12], [58], a PL and HCI design methodology that is aimed to "make it possible for people to express their ideas in the same way they think about them".…”
Section: A Language and Specification Qualitymentioning
confidence: 99%
“…It is essential to point out that while recent studies identified the need for human-centered design of programming languages [9], [12], [58] and formal methods techniques [37], there was no such study in the context of reactive synthesis. Moreover, there is a large body of work on HCI and synthesis; however, these works are focused mostly on inductive synthesis techniques such as programming by example (PbE) and programming by demonstration (PbD), which are fundamentally different than reactive synthesis from a formal specification.…”
Section: Introductionmentioning
confidence: 99%